The influence of pelting time on pelt characteristics in blue fox (Alopex lagopus) - Blomstedt, Leena; Jauhiainen, Lauri; Miettinen, Maija; Smeds, Kerstin (International Fur Animal Scientific Association (IFASA), 2004)
v ok